Comparison Analysis of Financial Performance of BUMN and Non BUMN Islamic Commercial Banks with RGEC Method - Hafiz Santak Taram; Isfandayani Isfandayani (Al Tijarah, 2022)
This research aims to analyze the comparison of the financial performance of BUMN Islamic Commercial Banks and Non BUMN Islamic Commercial Banks on the variables of Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) for the 2017-2020 period represented by the ratio of NPF, FDR, BOPO, GCG, ROA, ROE, and CAR. The results of this research show that of the 7 ratios analyzed, there are 5 ratios with significant differences between the financial performance of BUMN Islamic Commercial Banks and Non BUMN Islamic Commercial Banks during the 2017-2020 period, namely FDR, BOPO, GCG, ROA, and ROE. While the NPF ratio, CAR, and RGEC Composite Rating there is no significant difference between the financial performance of BUMN Islamic Commercial Banks and Non BUMN Islamic Commercial Banks during the 2017-2020 period. The last analysis on the consolidated financial performance assessment of all RGEC variables shows that the performance of BUMN Islamic Commercial Banks is not better than the performance of Non BUMN Islamic Commercial Banks where the average composite value for 4 years is the performance of BUMN Islamic Commercial Banks (80%), smaller than the composite value of the performance of Non BUMN Islamic Commercial Banks (86%).